Synthesis, characterization, physical and thermodynamic properties of diazobicyclo undecene based dicyanamide ionic liquids - Lethesh, K.C. (Elsevier, 2015)
Synthesis of new ionic liquids (ILs) based on diazobicyclo undacane (DBU) cation containing various alkyl groups such as ethyl, butyl, hexyl, octyl, decyl and tetradecyl group with dicyanamide anion were performed. The characterization of the ILs was carried out using NMR (1H and 13C) spectroscopy and elemental analysis. The water content, halide content and the thermal decomposition temperature of the synthesized ILs were determined. The density and viscosity of the ILs were measured in a large temperature range. The effect of temperature and alkyl spacer length on the physical properties such as density, viscosity and surface tension of the DBU based ILs were presented. The thermodynamic properties such as surface enthalpy and entropy, critical temperature and the total surface energy of the ILs were derived from their experimental surface tension and density data. Â© 2015 Elsevier B.V.